Exploring the Proficiency of Dayah's Teaching and Educational Staff for Sustainable Development in Aceh - Ilyas, Mukhlisuddin; Matsyah, Ajidar; Ismail, Zahrila (Institut Agama Islam Negeri Lhokseumawe, 2023)
Abstract: This study emerged from a crucial need to find out factors influencing educational staff in the implementation of Education for Sustainable Development in actual Dayah practices in Aceh. The objective of this research is to provide an extensive overview regarding how to boost the quality of teachers and educational employees in Aceh's Dayah. The study aims to create an effective step-by-step approach for increasing the quality of instructors and educational staff in Aceh's Dayah province. The study employs an explanatory qualitative method. Amongst the data resources are Dayah department leaders, program coordinators, and other employees and staff from Dayah educational departments. Despite the fact that academics possess diverse individual interests and motivations to participate in education for sustainable development, their engagement is influenced by factors such as the advantages of pursuing higher education, attending workshops and training, undertaking internships, and participating in capacity-building initiatives. However, resource limitations, including restricted financial means, limited access to information technology, and a lack of access to external organizational information, can potentially exacerbate the challenges mentioned earlier. This study provides a formulative model connected to disparities in policy and visions of sustainable development in regard to principles and roles of Dayah Education in enhancing the quality of educational programs. Abstrak: Urgensitas kebutuhan terhadap identifikasi faktor-faktor yang mempengaruhi tenaga kependidikan dalam melaksanakan Pendidikan untuk Pembangunan Berkelanjutan dalam praktik nyata Dayah di Aceh. Penelitian bertujuan untuk mendapatkan gambaran komprehensif terhadap peningkatan kualitas tenaga pengajar dan tenaga kependidikan dayah di Aceh. Penelitian berupaya menghasilkan model langkah efektif untuk meningkatkan kualitas tenaga pengajar dan tenaga kependidikan dayah di Aceh. Kajian ini difokuskan pada beberapa aspek, pertama aspek kebutuhan dan ketersediaan tenaga pendidik dan tenaga kependidikan dayah, kedua aspek kualifikasi tenaga pengajar dan tenaga kependidikan dayah, ketiga upaya dan kendala dalam peningkatan kualitas tenaga pendidik dan tenaga kependidikan dayah. tenaga kependidikan di Aceh, baik pesantren Salafiyah maupun Diniyah. Penelitian berjenis kualitatif eksplanatory. Sumber informan berasal dari kepala dinas dayah, koordinator program dan beberapa karyawan dan staf dinas pendidikan dayah. Studi ini menunjukkan bahwa meskipun akademisi mungkin memiliki minat dan motivasi pribadi untuk terlibat dalam pendidikan menuju kepada sustainabilitas pembangunan. Adapun faktor-faktor seperti manfaat melanjutkan pendidikan di tingkat universitas, lokakarya/ pelatihan, magang, peningkatan kapasitas, tetapi di antara manfaatnya ada faktor-faktor yang mempengaruhi seperti kurangnya sumber daya keuangan, keterbatasan akses teknologi informasi dan keterbatasan akses informasi ke lembaga eksternal. Penelitian ini memberikan model formulatif berkaitan dengan kebijakan perbedaan pandangan dan visi pembangunan berkelanjutan dalam aspek prinsip dan peran Pendidikan Dayah dalam meningkatkan mutu pendidikan pesantren di Aceh.